An Analysis of the Crucial Role of Religious Extremism Contributes to Afghanistan’s Political Instability - Abdul Wali Atif; Safi, Dr. Wadir; Safi, Dr. Zabihullah (American Journal of International Relations, 2024)
Purpose: Political stability in Afghanistan has been hindered by religious extremism. However, several parties have grown up within the country to oppose the government. These extremist groups employ suffering as a means of gaining political power rather than simply using religion Because Sunni, Shia, Hanafi, Wahhabi, and other religious individuals live and work to promote their religions, religious extremism has a significant effect on Afghanistan's political stability. This has led to numerous problems between the citizens and the government. Several explosions have happened in mosques targeting Shia. It is believed that non-Muslims are using this tactic to extend the ongoing conflict in Afghanistan distinctively. This paper aims to analyze the impact of religious extremism on political instability in Afghanistan. In this paper, the analysis is based on the fact that religious extremists have a great impact on the political stability of Afghanistan. Materials and Methods: The study emphasizes analytical and descriptive approaches to gathering and analyzing data, which is more consistent with qualitative studies. The primary approaches used to gather data for qualitative research encompass focus groups, observation, and interviews. Findings: The results of this study are as follows: (1) The analysis of religion is considered one of the important elements in Afghanistan, five categories of participants have different opinions about this response, 51% of respondents agree that religious extremes have an impact on Afghanistan political stability, 38% of participants strongly agree that religion has on impact on political stability in Afghanistan; (2) the supporting of militant groups has an impact on Afghan political instability, 5% of participants are neutral about this response, and 3% of the participants are strongly disagree about the above response. Implications to Theory, Practice and Policy: We recommend that the Afghan government strictly obey the rule of Islam and international partners should cooperate with Afghanistan in this field.